INTERTEKSTUAL DALAM CERITA AKU TIDAK MAU MARAH SERIAL BUKU CERITA PEMBANGUN KARAKTER ANAK KAJIAN INTERTEKSTUAL : JULIA KRISTEVA - Indriani Indah; Suarni Syam Saguni; Andi Sahtiani Jahrir (STKIP Subang, 2026)
This study aims to describe the form of opposition and transformation, in the children’s story Aku Tidak Mau Marah by Yudi based on Julia Kristeva’s Intertextuality theory. The study uses a qualitative descriptive method with library study and documentation techniques. Data in the form of dialogue, narrative, and events that show conflicting values and character changes. The results of the study show that opposition arises through the conflict between anger and patience, damage and repair, which forms the structure of the story’s conflict and Transformation is seen in the change in the character of the main character from an emotional attitude to moral awareness and responsibility. These two elements are interrelated and build a network of meaning that emphasizes the moral message of self-control and empathy. This study shows that Julia Kristeva’s Intertextuality theory is relevant to analyzing the formation of meaning in children’s literature.